Averrhoa carambola free phenolic extract ameliorates nonalcoholic hepatic steatosis by modulating mircoRNA-34a, mircoRNA-33 and AMPK pathways in leptin receptor-deficient db/db mice. Issue 12 (1st November 2017) - Pang, Daorui; You, Lijun; Zhou, Lin; Li, Tong; Zheng, Bisheng; Liu, Rui Hai
Abstract : Averrhoa carambola free phenolic extract ameliorates hepatic steatosis by modulating mircoRNA-34a, mircoRNA-33 and AMPK signaling. Abstract : The objective of the present study is to investigate the hepatic steatosis relieving effect of Averrhoa carambola free phenolic extract (ACF) on leptin receptor-deficient (db/db) mice and elucidate the modulation hepatic lipogenesis mechanisms. The serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) assays, accompanying hematoxylin and eosin (H&E) staining, were applied to identify the alleviation of liver histopathological changes. Serum and hepatic lipid assays, combined with oil red O staining, were used to investigate the amelioration of lipid accumulation. Further assessments by quantitative real-time PCR and western blot assays were used to elucidate the suppression of the fatty acid and triglyceride (TG) synthesis mechanisms underlying ACF protection. These results indicated that ACF treatment significantly reduced the liver TG of db/db mice ( p < 0.05). The mechanisms are partly through phosphorylation of AMPK α and down-regulation of SREBP-1c expression, and further down-regulation of FAS and SCD1 ( p < 0.05). In addition, the expression levels of mircoRNA-34a and mircoRNA-33, which modulate this signaling pathway, were significantly down-regulated by ACF treatment ( p < 0.05). Collectively, these results revealed that ACF exhibited a potent hepatic steatosis relieving effect partly by inhibiting the signal transduction of hepatic lipogenesis.